2017
DOI: 10.1001/journalofethics.2017.19.8.stas1-1708
|View full text |Cite
|
Sign up to set email alerts
|

Clowning as a Complementary Approach for Reducing Iatrogenic Effects in Pediatrics

Abstract: Hospitalized children who undergo painful procedures are more susceptible than others to experiencing iatrogenic effects, such as anxiety, pain, and severe stress. Clowns in clinical setting have been found to be effective in reducing children's experiences of these effects during hospitalization and before procedures. This article provides an overview of clowning in health care settings; reviews major studies conducted on clowning for hospitalized children, discussing evidence that clown interventions decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 29 publications
1
23
0
3
Order By: Relevance
“…Within the past two decades, there has been a surge of interest in investigating the effects of clown intervention in a large variety of clinical settings (Dionigi, 2018;Ford et al, 2014). However, only a few studies have investigated the personality traits of medical clowns, and they have been in specific countries (Dionigi, 2017;Dionigi & Canestrari, 2016). The main aim of this study was to investigate the relationship between levels of SPS, caregiving strategies and benevolent and corrective humour in two different groups: Italian and Israeli medical clowns.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the past two decades, there has been a surge of interest in investigating the effects of clown intervention in a large variety of clinical settings (Dionigi, 2018;Ford et al, 2014). However, only a few studies have investigated the personality traits of medical clowns, and they have been in specific countries (Dionigi, 2017;Dionigi & Canestrari, 2016). The main aim of this study was to investigate the relationship between levels of SPS, caregiving strategies and benevolent and corrective humour in two different groups: Italian and Israeli medical clowns.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, researchers have gained interest in the effectiveness of clowning in healthcare settings. Clowns in healthcare settings are organized into clown care units, made up of artists working alone or in pairs, and colloquially called various names: the most frequent are "clown doctors" and "medical clowns" (Dionigi, 2017). Clown doctors work in a large variety of…”
Section: Introductionmentioning
confidence: 99%
“…Jedną z metod zmniejszenia lęku i stresu wyżej opisanego jest działalność "doktorów klownów" rozwijająca się w wielu krajach, w tym w Polsce. Ta forma działalności została zapoczątkowana w 1986 roku w Stanach Zjednoczonych przez zawodowego klowna Michaela Christensena [15]. Z czasem powstały zespoły lub grupy (Clown Care Units) złożone z klownów, popularnie nazywanych "doktorami klownami" (clown doctors), którzy organizują pokazy i drobne zabawy dla chorych dzieci.…”
Section: Klown* W Szpitalu Dziecięcymunclassified
“…The clowns contribute to the hospital's mission through humour, laughter, imagination, and empathy while interacting with patients, their families, and staff (Koller & Gryski, 2008;Sridharan & Sivaramakrishnan, 2016). The methods of therapeutic clowning can facilitate children's healing process by helping them cope with their fear, sorrow, despair and stress (Bertini et al, 2011;Dionigi, 2017). Studies of therapeutic clowning have shown that clowns help to create a festive atmosphere in hospitals and distract kids during medical procedures (Bertini et al, 2011), encourage oral and silent communication (Linge, 2013) and positively influence mental health and manners (Koller & Gryski, 2008).…”
Section: Introductionmentioning
confidence: 99%